Variation in Bacterial Community Structures and Functions as Indicators of Response to the Restoration of Suaeda salsa: A Case Study of the Restoration in the Beidaihe Coastal Wetland - He, Changfei; Zheng, Li; Ding, Jinfeng; Gao, Wei; Li, Qian; Han, Bin; Li, Jingxi (Frontiers in Microbiology, 2022)
Microbes play an essential role in the restoration of degraded coastal wetlands. However, few studies have focused on the role of key bacteria in the restoration process. Here, Suaeda salsa was planted to recover the biodiversity in the degraded Beidaihe coastal wetland. We monitored omics and soil environmental factors to understand the complex relationship between the bacterial community and wetland health during the restoration period. After planting S. salsa in the degraded area, the soil quality was improved in the later stage of restoration (LPR). Bacterial α-diversity increased with restoration and was positively correlated with TOC. Proteobacteria is the dominant bacterial phylum during the restoration period, and Bacteroidetes, Planctomycetes, Gemmatimonadetes, and Acidobacteria were sensitive to the planting restoration. Random forest analysis picked 30 key OTUs, showing the key bacterial variation of successful restoration. The result indicated that the sum of the relative abundances of key bacterial OTUs was more than 2% in the health wetland. The β-diversity showed that the growth of S. salsa reshaped the soil bacterial community structure and function in the LPR, which recovered to the level in the control area. Putative biogeochemical functions showed that symbionts and aromatic compound degradation were dominant bacterial functions in the growth period of S. salsa. Our study proposed a new indicator to assess wetland health and the planting restoration of S. salsa increased bacteria groups with the ability of symbionts and aromatic compound degradation in the Beidaihe coastal wetland. This study expanded our knowledge of coastal wetland restoration and its ecological contributions.